A PATH TO PROSPERITY: OVERCOMING KNOWLEDGE BARRIERS IN EMBU’S AGRICULTURE - Mwangi , Kiprono Cheruiyot (Current Journal of Library and Information Sciences (CJLIS), 2023)
Knowledge, as defined by the Cambridge dictionary, encompasses the understanding and information acquired through experience or study. In the context of this study, we delve into the agricultural knowledge landscape in Embu County, Kenya, exploring the persistent gaps that challenge local farmers. These knowledge and information disparities not only affect Embu County but also resonate with broader implications for agricultural practices across various Kenyan counties. This research aims to identify these gaps and propose solutions to bridge the knowledge divide. The agricultural sector holds a pivotal role in Kenya’s economy, contributing directly and indirectly to the Gross Domestic Product (GDP). With a direct GDP contribution of 26% and an additional 27% through its linkages with manufacturing, distribution, and other service-related sectors, agriculture is a driving force of the nation’s economic stability. Furthermore, agriculture accounts for a significant portion of government revenue, supplying over 75% of industrial raw materials and more than 50% of export earnings. Additionally, it is the largest employment sector in the country, employing 60% of the total workforce. Notably, the majority of Kenya’s population, especially those residing in rural areas, rely on agricultural-related activities for their livelihoods. With over 80% of the population participating in this sector, the importance of agriculture in national development cannot be overstated. Consequently, the Kenyan government has consistently prioritized agriculture as a key instrument for promoting national development. This paper underscores the critical role of providing adequate agricultural information and implementing effective Knowledge Management (KM) practices to enhance the productivity of the agricultural sector. By addressing the knowledge gaps that hinder the efficiency and growth of the agricultural industry, this research aims to contribute to the broader goal of advancing national development and ensuring the well-being of the rural population